AN ANALYSIS OF THE IMPLEMENTATION OF THE PROSECUTOR'S REGULATION NUMBER 15 OF 2020 CONCERNING TERMINATION OF PROSECUTIONS BASED ON RESTORATIVE JUSTICE AGAINST THE ABUSIVE CRIMINAL ACT - Muammar Muammar; M. Irham Roihan (IAIN Bone, 2021)
The termination of prosecution in Erna Wilis’s case with Case Register Number PDM-44.SPEM/Eoh.2/07/2020 at the West Pasaman District Attorney Office, the author analyzes the basic considerations of the Public Prosecutor in implementing Restorative Justice, the suitability of the termination of the prosecution with the Prosecutor's Regulation (PERJA) Number 15 of 2020 concerning the termination of prosecution based on restorative justice and the obstacles faced by the Public Prosecutor. The research uses empirical juridical research methods with analytical descriptive studies using primary and secondary data. From the results of the analysis, it was concluded that the consideration of the Public Prosecutor was to apply Restorative Justice based on Article 14 of the Criminal Procedure Code letter h. Article 140 paragraph (2) letter a of the Criminal Procedure Code and Article 3 paragraph (2) letter e of PERJA Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. The termination of prosecution is in accordance with PERJA Number 15 of 2020 substantively and the obstacles faced lie in the suitability of the timing of the termination of prosecution based on restorative justice.